Pattern and degree of hearing loss in chronic suppurative otitis media (Bangladesh Journal of Otorhinolaryngology, 2011)
Objectives: To assess the pattern and degree of hearing loss in CSOM. Methods: A prospective study was carried out from January, 2007 to December, 2008 at the department of Otolaryngology-Head & Neck Surgery, BSMMU, Dhaka This study included 150 cases with 198 ears of CSOM including both tubo-tympanic and attico-antral variety excluding intracranial complications if any. Results: There were 81.31% cases of tubo-tympanic and 18.69% cases of attico-antral patients. Age of the patients was between 5-60 years, where male were 59.33% and female were 44.67%. Highest number of patients was in the age group of 21-30 years. Out of 198 ears, 102 had unilateral perforation and 96 had bilateral perforation. Most of the patients (53.33%) came from low income family and majority of them used to take their bath in the pond (29.34%) followed by tube-well (24.44%). Most of the patients had cleaning habit with clothes with sticks (53.5%).Majority of them resided in katcha house (52%) with poor hygienic condition. Central melleolar perforations were maximum (41.41%) and anterior central perforations were minimum (18.69%). According to sized of perforation, medium size central perforations were common (26.67%) It was shown that the site and sized of perforation affects the degree of hearing loss. Posterior central and attic perforations had greater hearing loss, 51.5 dB and 57.36 dB accordingly. On the basis of size, subtotal perforation had more hearing loss (54.54dB). It was also shown that posterior central perforation had greater hearing loss (51.5dB) than anterior- central (33.64dB) perforation. Hearing loss was more marked in patients with long duration of disease. In a history of 21-25years of disease, mean air conduction thresholds was 59 dB whereas of 0-5 years were 38.18 dB. Difference between them was statistically significant (t=5.88, p